2008
DOI: 10.1061/(asce)1084-0699(2008)13:8(729)
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Sand Depth on Domestic Wastewater Renovation in Intermittently Aerated Leachfield Mesocosms

Abstract: The depth of soil below the absorption trench of a septic system is considered an important factor in protection of groundwater. We examined the effects of depth on the ability of intermittently aerated sand-filled leachfield mesocosms to renovate domestic wastewater. Mesocosms ͑n =3͒ consisted of lysimeters with a headspace O 2 concentration maintained at 0.21 mol/ mol and containing 7.5, 15, or 30 cm of sand that were dosed with septic tank effluent every 6 h for 328 days ͑12 cm/ d͒. Sand depth had no effect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
7
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 22 publications
3
7
0
Order By: Relevance
“…The effluent's nitrate value was higher than that of the influent due to the nonpresence of anoxic conditions in the filter that will denitrify the nitrate to nitrogen gas. The mechanism of phosphorus removal is abiotic and involves sorption and binding of PO 4 -P with iron and aluminum oxides and oxyhydroxides on the surface of soil particles [5][6][7]. The average influent value of PO 4 -P was 4.15 ( ±0.8) mg/L while the average value of the effluent was 2.26 (± 0.81) mg/L.…”
Section: Resultsmentioning
confidence: 99%
“…The effluent's nitrate value was higher than that of the influent due to the nonpresence of anoxic conditions in the filter that will denitrify the nitrate to nitrogen gas. The mechanism of phosphorus removal is abiotic and involves sorption and binding of PO 4 -P with iron and aluminum oxides and oxyhydroxides on the surface of soil particles [5][6][7]. The average influent value of PO 4 -P was 4.15 ( ±0.8) mg/L while the average value of the effluent was 2.26 (± 0.81) mg/L.…”
Section: Resultsmentioning
confidence: 99%
“…The effects of ISA on nitrate dynamics may have taken place at shallow depths, such that the concentrations of NH 4 and NO 3 measured at 30 or 90 cm do not provide an accurate representation of inorganic N dynamics as a result of other production and consumption processes that can take place deeper within the soil profile, such as plant uptake, and microbial mineralization and/or immobilization. Using experimental mesocosms we have shown that total N removal appears to take place within the top 7.5 cm of aerated sand [15]. In addition, spatial and temporal variability may mask the effects of aeration on speciation of inorganic N below the STAs.…”
Section: Water Qualitymentioning
confidence: 92%
“…Previous studies of the composition of soil pore water below the infiltrative surface of conventional OWTS report that NO 3 accounts for 80 to 90% of inorganic N [12,13]. 15 ± 6 9 ± 1 II 47 ± 7 14 ± 9 24 ± 9 20 ± 13 20 ± 7 NH 4 I 23 ± 7 3 ± 3 1 ± 1 1 ± 1 1 ± 1 II 26 ± 5 0 ± 0 0 ± 0 1 ± 1 1 ± 3 NO 3 I 0 ± 0 8 ± 6 8 ± 6 12 ± 5 7 ± 1 II 1 ± 1 8 ± 7 12 ± 6 9 ± 8 11 ± 7 Total P I 12 ± 5 2 ± 1 2 ± 1 2 ± 1 2 ± 1 II 13 ± 2 3 ± 2 3 ± 1 3 ± 2 4 ± 2 DOC I 106 ± 24 12 ± 11 4 ± 2 5 ± 3 2 ± 3 II 118 ± 20 3 ± 3 2 ± 5 2 ± 3 6 ± 5 2 Cl -I 49 ± 20 42 ± 6 41 ± 5 2 ± 2 14 ± 14 II 45 ± 5 42 ± 16 41 ± 13 5 ± 7 15 ± 9 pH I 6.6 ± 0.1 6.7 ± 0.2 6.5 ± 0.1 6.7 ± 0.2 6.5 ± 0.3 II 6.6 ± 0.2 6.5 ± 0.2 6.5 ± 0.2 6.9 ± 0.1 6.5 ± 0.5 Fe 2+ I 0 ± 0 9 ± 1 0 ± 0 0 ± 0 0 ± 0 II 0 ± 0 2 ± 1 0 ± 0 0 ± 0 0 ± 0 Total N I 41 ± 7 37 ± 8 30 ± 6 14 ± 9 21 ± 9 II 40 ± 7 32 ± 11 33 ± 4 18 ± 15 14 ± 9 NH 4 I 21 ± 4 20 ± 9 1 ± 1 0 ± 0 0 ± 0 II 22 ± 4 20 ± 8 1 ± 1 0 ± 0 0 ± 0 NO 3 I 0 ± 0 9 ± 4 22 ± 7 9 ± 7 12 ± 6 II 0 ± 0 1 ± 1 19 ± 6 5 ± 4 5 ± 4 Total P I 9 ± 4 7 ± 4 2 ± 1 2 ± 1 2 ± 1 II 12 ± 3 9 ± 2 3 ± 2 3 ± 1 4 ± 3 DOC I 105 ± 23 63 ± 11 37 ± 9 36 ± 3 6 ± 3 Previous mesocosm-scale evaluation of the effects of intermittent soil aeration of STAs on nitrogen transformations have shown high levels of NO 3 and nearly complete absence of NH 4 in water draining below 30 cm of sand or soil, in contrast to unaerated mesocosms [8,14,15]. Furthermore, drainage water from intermittently aerated mesocosms had a considerably lower pH than unaerated treatments [8,14,15].…”
Section: Water Qualitymentioning
confidence: 99%
“…A varied set of design configurations are now widely used to reduce environmental and public health risks (Amador et al 2008;Oakley et al 2010). In water-limited locations, grey water (household wastewater exclusive of toilet waste) effluent is treated and applied as irrigation to supplemental landscape irrigation (Waskom and Kallenger 2009).…”
Section: • Developing and Implementing On-farmmentioning
confidence: 99%